Estudo comparativo da regulação da apoptose mediada por agentes Pró e Anti-Inflamatórios em granulócitos humanos - Luz, Ricardo Alves (2007)
Programmed cell death, recognizable through the morphological features of apoptosis, is a central mechanism in the regulation of cell populations in metazoans, which in the immune system makes possible the resolution of inflammatory processes, the fine tuning of clonal expansion and the prevention of autoimmunity. This study is concerned with the mechanisms through which apoptosis is modulated by exogenous agents, in two different classes of human granulocytes (neutrophils and eosinophils), that share a common origin in the bone-marrow, as well as many morphological and functional features, but carry out different roles in host defense. We have drawn from experimental studies on the regulation of apoptosis in developing murine eosinophils, carried out by our research team, along with laboratory observations on the regulation of apoptosis in mature human granulocytes, done by other groups, to build the hypothesis that effects and interactions observed with murine developing eosinophils could be duplicated with the same agents on mature human neutrophils, but not eosinophils. To test this hypothesis, we have initially evaluated, by morphology and by flow cytometry following staining with Annexin V and propidium iodide, the effects of: a) all-trans Retinoic Acid (ATRA); b) dexamethasone; c) ATRA and dexamethasone. Purified granulocyte populations from the blood of healthy donors were incubated up to 20 h in medium, without survival-promoting or apoptosis-promoting factors, or in the presence of ATRA and dexamethasone, alone or in association. Neutrophils and eosinophils underwent spontaneous apoptosis which dependent on the culture density, as reported in previous studies. ATRA strongly induced apoptosis in neutrophils, dose-dependently. By contrast, dexamethasone protected neutrophils from spontaneous apoptosis. Dexamethasone further protected neutrophils from apoptosis induced by ATRA. These findings confirm that the study was carried out in conditions comparable to those of previous studies, and document a proapoptotic effect of ATRA hitherto undescribed in human neutrophils, as well as a novel interaction between ATRA and dexamethasone in this granulocyte lineage. Subsequently, we evaluated the effects of indomethacin, which enhances eosinophil production in murine-bone marrow culture. Indomethacin strongly induced apoptosis in human neutrophils, in the absence of exogenous agents, an observation that is also novel. These findings indicate that: a) although human neutrophils can present responses to ATRA and dexamethasone similar to those in developing murine eosinophils, but distinct from those of mature human eosinophils, this similarity does not extend to the effects of other agents; b) the signaling cascades initiated by ATRA and dexamethasone in mature human neutrophils present strong interactions (cross-talk), the mechanism of which needs to be established; c) indomethacin can present, in this setting, proapoptotic effects distinct from those reported for other nonsteroidal anti-inflammatory drugs, such as aspirin and sodium salicilate